2014
DOI: 10.1371/journal.pntd.0003082
|View full text |Cite
|
Sign up to set email alerts
|

Toxocara Seroprevalence among Clinically Healthy Individuals, Pregnant Women and Psychiatric Patients and Associated Risk Factors in Shandong Province, Eastern China

Abstract: BackgroundToxocarosis is a widespread zoonosis caused by the ascarid nematodes Toxocara canis and Toxocara cati, which primarily infect dogs and cats, respectively. Most human infections with Toxocara are asymptomatic; however, some infected individuals may develop a serious illness and even death. Nevertheless, epidemiological knowledge regarding the prevalence and risks associated with Toxocara infection is limited in China. Therefore, we performed a cross-sectional pilot study and estimated the seroprevalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
4
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 28 publications
4
43
4
6
Order By: Relevance
“…Several studies have concluded that the cost of human toxocariasis is underestimated and understanding of its global impact remains poor because of the inadequacy of clinical awareness and an obvious lack of efficacy of laboratory, clinical and treatment interventions [1,2,4,[9][10][11]. To the author's knowledge, to date, no bibliometric studies have assessed Toxocara and toxocariasis research over time at the global level.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have concluded that the cost of human toxocariasis is underestimated and understanding of its global impact remains poor because of the inadequacy of clinical awareness and an obvious lack of efficacy of laboratory, clinical and treatment interventions [1,2,4,[9][10][11]. To the author's knowledge, to date, no bibliometric studies have assessed Toxocara and toxocariasis research over time at the global level.…”
Section: Introductionmentioning
confidence: 99%
“…Significantly, T. canis larvae can migrate throughout the human body and encyst as arrested larvae in the muscles and nervous system causing visceral larva migrans, ocular larva migrans or neural larva migrans (Kayes, 1997;Despommier, 2003;Caldera et al, 2013). Epidemiological studies in some African, Asian and Latin American countries indicated a high prevalence of this zoonotic disease, ranging from 12.3% to 93% (Schoenardie et al, 2013;Macpherson, 2013;Cong et al, 2014;Moreira et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A study in Serbia revealed a seroprevalence of 13% for Toxocara infection with a significant difference between sex gender (more common in women), but not among the age groups . Yet, a few studies reported that the seropositivity to Toxocara increases by age …”
Section: Discussionmentioning
confidence: 99%
“…29 Yet, a few studies reported that the seropositivity to Toxocara increases by age. 21,22 The association between Toxocara infection and dog or cat ownership has been documented. Study of Cong et al 22 Jilin provinces in China, the seroprevalence of Toxocara infection among the study population was found to be 19.3% 23 and exposure to soil and keeping dogs at home were among the factors which were associated with Toxocara infection.…”
Section: A Few Examples Of Numerous Studies About the Seroprevalence Ofmentioning
confidence: 99%
See 1 more Smart Citation